Comparison of chimeric antigen receptor‐T cell‐mediated cytotoxicity assays with suspension tumor cells using plate‐based image cytometry method. Issue 1 (3rd August 2022) - Sun, Yu‐Jun; Chen, Yi‐Chun; Hua, Wei‐Kai; Wu, Sareina Chiung‐Yuan; Chan, Leo Li‐Ying
Abstract: In the recent decade, chimeric antigen receptor (CAR)‐T cell therapy has revolutionized strategies for cancer treatments due to its highly effective clinical efficacy and response for B cell malignancies. The success of CAR‐T cell therapy has stimulated the increase in the research and development of various CAR constructs to target different tumor types. Therefore, a robust and efficient in vitro potency assay is needed to quickly identify potential CAR gene design from a library of construct candidates. Image cytometry methodologies have been utilized for various CAR‐T cell‐mediated cytotoxicity assay using different fluorescent labeling methods, mainly due to their ease‐of‐use, ability to capture cell images for verification, and higher throughput performance. In this work, we employed the Celigo Image Cytometer to evaluate and compare two CAR‐T cell‐mediated cytotoxicity assays using GFP‐expressing or fluorescent dye‐labeled myeloma and plasmacytoma cells. The GFP‐based method demonstrated higher sensitivity in detecting CAR‐T cell‐mediated cytotoxicity when compared to the CMFDA/DAPI viability method. We have established the criteria and considerations for the selection of cytotoxicity assays that are fit‐for‐purpose to ensure the results produced are meaningful for the specific testing conditions.